2006
DOI: 10.2527/jas.2005-414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spray-dried porcine plasma and plant extracts on intestinal morphology and on leukocyte cell subsets of weaned pigs1

Abstract: We evaluated the effects of a 6% spray-dried porcine plasma (SDPP) and a plant extracts mixture (XT; 5% carvacrol, 3% cinnamaldehyde, and 2% capsicum oleoresin) on the productive performance, intestinal morphology, and leukocyte cell subsets of early-weaned pigs compared with a control group. Morphometry of the jejunum, ileum, and colon, and immune cell analysis of blood, ileocolic lymph node (LN), and ileal Peyer's patches were done in 24 weaned pigs (20 +/- 2 d) at 19 or 21 d postweaning. Although SDPP and X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
111
3
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 23 publications
16
111
3
6
Order By: Relevance
“…Neutrophil polymorphonuclear leukocytes (granulocytes) are responsible for the non-specific immune response and mainly for the share of phagocytosis intro-defence of the host to infectious and inflammatory actions (Escribano et al 2005). Higher PA in EG2 can be explained by the combination of essential oils in Xtract (carvacrol from oregano, cinnamaldehyde from cinnamon and capsaicine from chilli peppers); it seems to have a longer immunomodulatory effect (Milos et al 2000;Nofrarías et al 2006). Concerning the values of VFA in caecum, Gidenne et al (1998) reported that the VFA concentration changed slowly with the age of the rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil polymorphonuclear leukocytes (granulocytes) are responsible for the non-specific immune response and mainly for the share of phagocytosis intro-defence of the host to infectious and inflammatory actions (Escribano et al 2005). Higher PA in EG2 can be explained by the combination of essential oils in Xtract (carvacrol from oregano, cinnamaldehyde from cinnamon and capsaicine from chilli peppers); it seems to have a longer immunomodulatory effect (Milos et al 2000;Nofrarías et al 2006). Concerning the values of VFA in caecum, Gidenne et al (1998) reported that the VFA concentration changed slowly with the age of the rabbit.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with spray-dried plasma (SDP) 7 improves the intestinal homeostasis reducing the basal activation of the immune system (3,4). Furthermore, SDP feed can reduce intestinal inflammation in unchallenged weaned pigs, as indicated by decreased intraepithelial lymphocytes and lamina propria cell density in the large intestine (5).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue samples were dehydrated and embedded in paraffin wax, sectioned at 4 m, and stained with hematoxylin and eosin. Morphological measurements were performed with a light microscope (BHS; Olympus, Spain), according to published parameters (21). Analytical methods.…”
Section: Methodsmentioning
confidence: 99%